Community-Based Approaches to Tackling Illegal Wildlife Trade—What Works and How Is It Measured? - Wilson-Holt, Olivia; Roe, Dilys (Frontiers in Conservation Science, 2021)
The illegal wildlife trade (IWT) is a global issue that threatens the conservation of many species of fauna and flora and affects the livelihoods of people who are dependent upon wildlife. By far the most common approach to tackling IWT is to enhance law enforcement, including arming rangers and tougher penalties for perpetrators. Yet, critics of this approach argue that efforts to reduce IWT in source countries are likely to fail without the involvement of local people. However, little is known about the effectiveness of community-based approaches to tackling IWT or how this is being measured. We used information from the www.PeoplenotPoaching.org learning platform to analyze over 100 case studies of community-based anti-IWT interventions to understand what proportion have been effective and how this has been measured. We present a typology of frequently reported outcomes, what was measured and by what methods. We show that effectiveness in community-based anti-IWT interventions is measured in a number of ways and by a variety of methods. Our findings suggest that conservation practitioners more frequently implement activities to measure conservation outcomes in comparison to livelihood outcomes, which has implications for how we consider if a community-based anti-IWT project has been effective. We recommend that future community-based anti-IWT projects build in more robust monitoring and evaluation activities to measure how livelihood benefits impact local communities given their support is crucial to achieving long-term conservation success.